Vitamin B12 and predatory behavior in nematodes - Lo, W.; Sommer, R. (2022)
The round worms or nematodes are the largest phylum of animals with an estimated species number of more than one million. Nematodes have invaded all ecosystems and are known from all continents including Antarctica. Parasitic species infest plants, animals and humans often with high host-specificity. Free-living species are known from marine, fresh water and soil systems, the latter of which contain many culturable species. This includes Caenorhabditis elegans, a species that was developed as one of the most prominent model systems in modern biology since the 1960ies. Pristionchus pacificus is a second nematode model organism that can easily be cultured in the laboratory. This species shows a number of complex traits including omnivorous feeding and the capability of predation on other nematodes. Predation depends on the formation of teeth-like denticles in the mouth of P. pacificus, structures unknown from C. elegans and most other nematodes. Here, we review the current knowledge about the role of vitamin B12 for the predatory behavior in P. pacificus and correlate its role with that on the physiology and development in C. elegans.